Effects of an assertive behaviour program on the reduction of anxiety in future teachers and preschool teachers - Milovanović , Radmila (Technium Social Sciences Journal, 2021)
Starting from the significance of assertiveness in the context of the professional competencies of teachers and preschool teachers and the knowledge of the connection between assertiveness and anxiety, the aim of this paper was to examine the possibility of reducing anxiety in students, future preschool teachers and teachers, by implementing an assertive behaviour program. The total sample consisted of 120 students of the Faculty of Education of the University of Kragujevac. The following instruments were used: The Assertiveness Assessment Scale and The Anxiety Assessment Scale. The research design involved three stages: 1.) initial assessment of anxiety and selection of students with high scores on the anxiety scale; 2.) implementation of the assertive behaviour exercise program (2 introductory theoretical lessons and 8 exercise lessons); and 3.) final assessment of anxiety and assertiveness. Significant differences were obtained, in the scores on the applied anxiety scale, between the initial and the final assessment (t=27.855; p<0.000). The results point to the need and justifiableness of planned activities aimed at providing additional support to anxious students during the course of their studies, in order for them to strengthen control and master the skills of reducing anxiety in social contexts.